L-Type calcium channels mediate water intake induced by angiotensin injection into median preoptic nucleus - Saad, W. A.; Motta Siqueira Guarda, I. F.; de Arruda Camargo, L. A.; Faria Brizola dos Santos, T. A. (Elsevier B.V., 2006)
Calcium ions are widely accepted as critically important in responses of neurons to a stimulus. We have show previously the central involvement of angiotensin II (ANGII) in water intake. This study determined whether voltage-dependent calcium channels are involved in ANGII-induced behavioral drinking implicating nitrergic mechanism. The antidipsogenic actions of L-type calcium channel antagonists nifedipine, on ANGII-induced drinking behavior were studied when it is injected into the median preoptic nucleus (MnPO). The influence of nitric oxide (NO) on nifedipine antidipsogenic action was also studied by utilizing the N-W-nitro-L-arginine methyl ester (L-NAME) a constitutive nitric oxide synthase inhibitor constitutive (cNOSI) and 7-nitroindazol (7-NIT) a specific neuronal nitric oxide synthase inhibitor (nNOSI) and L-arginine a NO donor. Rats 200-250 g, with cannulae implanted into MnPO, pre-treated into MnPO with either nifedipine, followed by ANGII, drank significantly less water than controls during the first 15 min after injection. However, L-NAME potentiated the dipsogenic effect of ANGII that is blocked by prior injection of nifedipine and L-arginine. 7-NIT injected prior to ANGII into MnPO also potentiated the dipsogenic effect of ANGII but with a less intensity than L-NAME that it is also blocked by prior injection of nifedipine. The results described in this paper provide evidence that calcium channels play important roles in the ANGII-induced behavioral water intake. The structures containing NO in the brain such as MnPO include both endothelial cells and neurons might be responsible for the influence of nifedipine on dipsogenic effect of ANGII. These data shows the correlation between L-type calcium channel and a free radical gas NO produced endogenously from amino acids L-arginine by endothelial and neuronal NO synthase in the control of ANGII-dipsogenic effect. This suggests that an L-type calcium channel participates in both short- and longer-term neuronal actions of ANGII by nitrergic way. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: angiotensin II; calcium channel; nitric oxide drinking behavior; MnPO